2014
DOI: 10.3892/or.2014.3618
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid strongly enhances delayed intracellular production of reactive oxygen species (ROS) generated by ionizing irradiation: Quantitative analyses and visualization of intracellular ROS production in glioma cells in vitro

Abstract: Abstract. Postoperative adjuvant radiotherapy has important roles in multimodal treatment for highly aggressive malignant gliomas. Previously, we demonstrated that multi-dose ionizing irradiation with repetitive administration of 5-aminolevulinic acid (5-ALA) enhanced the host antitumor response and strongly inhibited tumor growth in experimental glioma. However, the mechanism of the radiosensitizing effect of 5-ALA is not known. Ionizing irradiation not only causes reactive oxygen species (ROS) formation init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 37 publications
8
23
0
Order By: Relevance
“…In the indirect reaction, radiation induces water radiolysis and generates ROS, including superoxide, hydroxyl radicals and hydrogen peroxide, which damage DNA and cell organelles (37,38). Previous studies have reported that 5-ALA-induced PpIX serves an important role in the production of ROS (31,33). The radiosensitivity induced by HpD and photofrin is caused by higher intracellular concentrations of porphyrin compounds relative to 5-ALA-induced PpIX (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the indirect reaction, radiation induces water radiolysis and generates ROS, including superoxide, hydroxyl radicals and hydrogen peroxide, which damage DNA and cell organelles (37,38). Previous studies have reported that 5-ALA-induced PpIX serves an important role in the production of ROS (31,33). The radiosensitivity induced by HpD and photofrin is caused by higher intracellular concentrations of porphyrin compounds relative to 5-ALA-induced PpIX (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that HpD and photofrin also act as significant radiosensitizers (28,29). Although the radiosensitizing effect of 5-ALA is controversial, it has been demonstrated in glioma and melanoma by numerous studies (3033). The mechanisms remain unclear; however, a previous study has reported that the initial reactive oxygen species (ROS) generated from water radiolysis and delayed production of ROS in mitochondria following ionizing irradiation enhance radiosensitivity (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 5-ALA with subsequent intracellular PpIX accumulation also increases keV or MeV irradiation cytotoxicity in a variety of contexts [22][23][24][25][26][27][28][29][30][31][32][33]. A robust, detailed physics-based explanation for this is currently lacking, but ample preclinical data attest to the basic mechanism of PpIX interacting with keV photons to generate cytotoxicity greater than the same irradiation given without 5-ALA where 5-ALA serves as a radiosensitizer.…”
Section: -Ala Enhances Kev and Mev Cytotoxicitymentioning
confidence: 99%
“…A robust, detailed physics-based explanation for this is currently lacking, but ample preclinical data attest to the basic mechanism of PpIX interacting with keV photons to generate cytotoxicity greater than the same irradiation given without 5-ALA where 5-ALA serves as a radiosensitizer. These twelve recent studies drive the imperative to study 5-ALA during the irradiation of DIPG [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: -Ala Enhances Kev and Mev Cytotoxicitymentioning
confidence: 99%